Sculpting on polymers using focused ion beam - Moon, M. -W.; Her, E. -K.; Oh, K. H.; Lee, K-R.; Vaziri, A. (ELSEVIER SCIENCE SA, 2008)
It has been recently shown that ordered wrinkles can be created on the Surface of polymers using focused ion beam irradiation. Here, we provide an overview of the techniques developed for controlled creation of nanoscale wrinkling patterns on the polymer surface using focused ion beam. Moreover. some of the key experimental challenges for precise fabrication of wrinkling patterns were investigated by exploring the role of pixel dwell time and fluence on the morphology of the created patterns. It was demonstrated that precise modification of the polymeric surface can be achieved with high pixel dwell time at low ion fluence. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: SURFACE MODIFICATION; DWELL TIME; SILICON; FILMS; BOMBARDMENT; IRRADIATION